Research Methods in Orthodontics A Guide to Understanding Orthodontic Research - Eliades, Theodore. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
The orthodontic literature includes many articles on basic science and engineering research techniques, but clinicians are typically unfamiliar with the principles underlying these techniques and may also lack the background knowledge required for a full appreciation of their role. This book comprehensively reviews a wide array of the research methods most frequently encountered in the literature, encompassing the areas of materials science and clinical and biological research. The various methods and techniques are carefully described, and their indications and limitations are explained. All of the information is up to date, reflecting latest developments. For practicing professionals, Research Methods in Orthodontics will be an ideal introduction to instrumental analysis and basic science research methods in the field. It will also serve as an excellent reference guide for researchers. By familiarizing orthodontists with the basics of research methods, the book will boost their ability to keep pace with developments in treatment approaches, materials, and techniques and assist in the transfer of relevant future findings into practice.